What Do We Compare When We Compare Religions?: Philosophical Remarks on the Psychology of Studying Comparative Religion Abroad - Irvine, Andrew B. (Teaching theology and religion, 2015)
The issue of comparison is a vexing one in religious and theological studies, not least for teachers of comparative religion in study abroad settings. We try to make familiar ideas fresh and strange, in settings where students may find it hard not to take "fresh" and "strange" as signs of existential threat. The author explores this delicate pedagogical situation, drawing on several years' experience directing a study abroad program and on the thought of figures from the Western existentialist tradition and Chinese Confucian philosophy. The article focuses particularly on "oh events" - defined as moments when one learns one has something to learn and something to unlearn. The author argues that the experience of shame that is typical of oh events can become a valuable resource for cross-cultural learning and personal transformation, if teachers assist students to reflect on the experience as a sign of differing, but potentially harmonizable, cultural expectations. This essay is published alongside of six other essays, including a response from John Barbour, comprising a special section of the journal (see Teaching Theology and Religion 18:1, January 2015).